Memory, Executive Skills, and Psychosocial Phenotype in Children with Pharmacoresponsive Epilepsy: Reactivity to Intervention - Schaffer, Yael; Ben Zeev, Bruria; Cohen, Roni; Shufer, Avinoam; Geva, Ronny (Frontiers in Neurology, 2017)
Background: Recent studies on pharmacoresponsive epilepsies demonstrate specific memory, executive functions and psychosocial deficits in this group. These deficits are often under-treated and little is known about the neuropsychological factors that may support moderation of the deficits through intervention. The aim of this study was to explore the effects of a structured cognitive behavioral group intervention on both memory and emotional domains, and evaluate the factors influencing its efficacy. Methods: This feasibility study implemented a newly designed intervention for children with pharmacoresponsive epilepsies (N=33, aged 9-14 years, 51% girls), hypothesizing that memory and psychosocial symptoms in children with pharmacoresponsive epilepsies are sensitive to intervention using structured memory and psychosocial modules in a weekly group session setting. Comparable memory and psychosocial assessments were used to evaluate performance at baseline and post-intervention. Results were compared to age and education-matched healthy controls (N=27, aged 9-14 years). Results: Pre-Post intervention comparisons show improvements in STM (p<0.01, Ƞ²=0.358), optimism (p<0.05, Ƞ²=0.245) and self-efficacy (p<0.05, Ƞ²=0.164). Unique negative relations between memory deficits and psychosocial phenotype were seen in epilepsy patients and not in controls in response to the intervention. Executive functions moderated this intervention effect (p<0.05, Ƞ²=0.252), whereas psychosocial status and pharmacological profile did not. Conclusions: Cognitive behavioral therapy focusing on memory and psychosocial perceptions for children with pharmacoresponsive epilepsies seem promising, with greater improvement in memory and psychosocial functioning in children with more affected executive functions.